HUBUNGAN KARAKTERISTIK PASIEN RAWAT JALAN TUBERKULOSIS PARU TERHADAP TINGKAT KEPATUHAN MINUM OBAT DI PUSKESMAS SAWIT SEBERANG - Grace Anastasia br Ginting; Eva Diansari Marbun; Andre Prayoga; Rosmeri Br Karo (Universitas Haji Sumatera Utara, 2022)
Pulmonary tuberculosis is an infectious disease, so non-adherence to treatment will result in treatment failure, risk of death, and cause more patients to become resistant. This study aims to determine the relationship between the characteristics of pulmonary tuberculosis outpatients on the level of medication adherence in Sawit Seberang Public Health Center. This research was conducted with a cross sectional survey research method. The instrument used in this study was a validated questionnaire containing 8 questions about patient compliance and pill count data by calculating the patient's remaining medication. A total of 45 patients were used as respondents who had pulmonary tuberculosis. Data were analyzed using the Statistical Package for the Social Sciences (SPSS) version 18 program. The results showed that the level of compliance of pulmonary tuberculosis patients in Sawit Seberang Public Health Center based on the questionnaire was high, namely 62.2%, and the compliance level of pulmonary tuberculosis patients in Sawit Seberang Public Health Center based on the Pill Count was perfect, namely 93.3%. Patient characteristics (gender, age, education, and occupation) did not affect the level of compliance of patients taking pulmonary tuberculosis drugs with p values of 0.462, 0.527, 0.260, 0.482 respectively. This study proves that the level of compliance of pulmonary tuberculosis patients in Sawit Seberang Public Health Center based on the questionnaire is high and based on the Pill Count is perfect. Patient characteristics (gender, age, education, and occupation) did not affect the patient's level of compliance to taking pulmonary tuberculosis drugs.